A declaration for international relations (based on Islamic Sufi teachings). Issue 4 (10th July 2017) - Bidabad, Bijan
Abstract : Purpose: Establishing peace, security and discipline for individuals, nations and states in contemporary international order is of the highest importance at the present time. Regularization should be done through approaching natural rights of individuals and also through observing humanistic characteristics and ethics. The aim of this paper is to introduce a legal base to promote international relations. Design/methodology/approach: A draft for International Relation Declaration based on Islamic Sufi teachings has been compiled, and actually it is an abstract of an extended survey on the subject and opinions in relation to the current international problems. Findings: This draft has been codified in three main topics of public international law, foreign policy and diplomacy. Research limitations/implications: To conclude the draft, it should be scrutinized by many scholars in different disciplines, in the next step. Practical implications: As the mystical characteristics of Sufism and Gnosticism of all religions (Tariqa) are all united and based upon love towards the Creator and consequently towards the creatures of God, these provisions could be agreed upon and put into practice. Social implications: Delicateness, truthfulness and righteousness of Islamic Sufism, which is the gist of all those elites' divine messages for thousands of years, one after another, can be of a great help to regulate international relations. Originality/value: International Law scholars have not looked at this subject matter from the Sufism viewpoint. This paper will shed a light on this point of view from other angles related to the international law such as politics, law and institutions.